Perbandingan Peningkatan Hasil Belajar Mahasiswa pada Materi Peluang melalui Pendekatan Humanisme dan Esensialisme - Fransiska Gusman; Alse Ona Sabat (Mandalika Mathematics and Educations Journal, 2026)
This study aims to compare the improvement in students' learning outcomes regarding probability topics when taught using humanism and essentialism learning approaches. The study employed a quantitative approach, specifically a comparative research method utilizing a pretest-posttest comparison group design. The subjects consisted of 30 students enrolled in a Statistics course covering probability, divided into two learning groups. The first group received instruction based on the humanism approach, while the second group was taught using the essentialism approach. The research instrument was an essay-type learning outcome test—validated for content—which served as both the pretest and posttest. Data were analyzed descriptively using normalized gain (N-Gain) scores to determine the extent of improvement in student learning outcomes. The results indicate that both approaches successfully improved student learning outcomes in probability. The average N-Gain score for the humanism group was 0.68, which was higher than the 0.50 score recorded for the essentialism group. Based on these findings, the humanism approach yielded a greater improvement in learning outcomes compared to the essentialism approach for the probability topic.